The Influence of Facebook Usage on Sales Performance: The Mediating Role of Employees’ Service Behaviours - Kosiba, J. P. B. (University of Ghana, 2016)
The purpose of this study is to examine the influence of Facebook usage on sales performance and explore whether an employee's service behaviour has a mediating effect on the relationship between Facebook usage and sales performance. This study employed an explanatory research design to explain the cause-and-effective relationship among Facebook usage, an employee's service behaviour and sales performance. Self-administered questionnaires and the use of a uniform resource locator (URL) through google forms comprising three sections was employed in collecting data. The target population for this study was businesses that were performing well on Facebook during the sample time frame. After a three month period of data collection, one hundred and one (101) questionnaires were valid for statistical analyses. The Partial Least Square (PLS) method was used to test the hypothesis. The study revealed that Facebook usage has a significant influence on customer-base relationship performance and financial performance. Businesses predominantly use Facebook to increase their brand visibility and to develop customer relationships. However, using Facebook for visibility has no significant influence on its relationship with customer-base relationship performance and financial performance. An employee's service behaviour was found to have a partial mediating effect on the relationship between Facebook usage and sales performance. This study contributes with new knowledge regarding the potential and limitations of the use of Facebook in marketing and sales. Substantial usage of Facebook seems to be primarily directed towards visibility and relationship development. Use of Facebook for information search is limited but significant in improving sales performance. The study provides evidence of how an employees' extra role services behaviour helps explain sales performance
Theses (MPhil.) - University of Ghana, 2016